The Influence of Islamic Branding, Price, and Online Customer Reviews on Purchase Decision for Wardah Skincare: A Study on Islamic Economics Student in Surabaya - Wienda Ayu Kusumawardhani; Moh. Farih Fahmi (Formosa Journal of Multidisciplinary Research, 2024)
The beauty industry, especially skincare, is currently experiencing significant progress so that skin care producers are required to be innovative and creative in their marketing strategies. With so many choices available to consumers, it becomes important for them to make the right decision when choosing skin care products. In connection with this trend, the author conducted research to investigate the impact of Islamic branding, price, and online customer reviews on purchasing decisions for Wardah skin care among Islamic Economics Students in Surabaya. This research uses quantitative methods, collecting primary data through distributing questionnaires from 160 respondents using purposive sampling. Data analysis was carried out using Structural Equation Modeling – Partial Least Square on SmartPLS 4. The findings showed that Islamic branding did not have a significant influence on purchasing decisions, while price and online customer reviews had a significant influence on Wardah skincare purchasing decisions. This shows that consumers, especially Islamic Economics Students in Surabaya, prioritize price and online reviews over the Islamic image of the Wardah skin care brand when making purchasing decisions.